Perancangan Buku Panduan Website dan virtual tour Desa Pematang Gajah Sebagai Media Promosi Agrowisata dan UMKM - Maisya Huwaida, Abelia; Febrisa Anggraini, Nabila; Iza Sofiani, Amanda; Suniyyah, Nabila; Arsa, Daniel (Journal of Comprehensive Science, 2025)
Low personal hygiene during menstruation in adolescent girls can cause various This guidebook is designed to help the people of Pematang Gajah Village in managing websites and virtual tours as a medium for promoting agro-tourism and MSMEs in the village. The use of information and communication technology, especially websites and virtual tours, is important to introduce local potential to a wider audience. This guidebook aims to provide technical instructions for the use of the Pematang Gajah Village website and the management of virtual tours that can increase the attractiveness of the village as a tourist destination. Through a Research and Development (R&D) approach, the book consists of various important sections, including an explanation of the website's features and a virtual tour. This book is expected to increase public understanding of the use of digital technology, simplify the promotion process, and encourage the improvement of digital skills that can contribute to economic development and tourism in Pematang Gajah Village.